Jacqueline in Paris : [large type] a novel - Mah, Ann (Harper Large Print, an imprint of HarperCollins Publishers, 2022)
In September 1949 Jacqueline Bouvier arrives in postwar Paris to begin her junior year abroad. She's twenty years old, socially poised but financially precarious, and all too aware of her mother's expectations that she make a brilliant match. Before relenting to family pressure, she has one year to herself far away from sleepy Vassar College and the rigid social circles of New York, a year to explore and absorb the luminous beauty of the City of Light. Jacqueline is immediately catapulted into an intoxicating new world of champagne and châteaux, art and avant-garde theater, cafés and jazz clubs. She strikes up a romance with a talented young writer who shares her love of literature and passion for culture, even though her mother would think him most unsuitable. But beneath the glitter and rush, France is a fragile place still haunted by the Occupation. Jacqueline lives in a rambling apartment with a widowed countess and her daughters, all of whom suffered as part of the French Resistance just a few years before. In the aftermath of World War II, Paris has become a nest of spies, and suspicion, deception, and betrayal lurk around every corner. Jacqueline is stunned to watch the rise of communism, anathema in America, but an active movement in France, never guessing she is witnessing the beginning of the political environment that will shape the rest of her life, and that of her future husband.